Analysis of Adding Durian Skin Fiber as a Coarse Aggregate Additive in Concrete - Arifin, Muhammad Fahmi; Prabowo, Yudi Setio; Mahendra, Muhammad Oka (Jurnal Teknik Sipil, 2026)
The extensive use of concrete has accelerated the depletion of natural aggregates and increased the accumulation of underutilized agricultural waste. Durian peel is a biomass residue with potential application in cement-based materials. This study investigates the feasibility of using untreated durian peel fiber as an additive to coarse aggregate in K-175 grade concrete. Unlike previous studies that primarily focus on chemically treated natural fibers, this research establishes the baseline performance of untreated durian peel fiber to identify its practical limitations. An experimental program was conducted using fibers sourced from Serang and Cilegon, Indonesia, processed through cleaning, cutting, and drying. Concrete mixtures were prepared with fiber contents of 0%, 2%, and 4% by weight of coarse aggregate. Twelve 150 mm cube specimens were tested for slump and compressive strength at curing ages of 3 and 7 days. Results indicate that increasing fiber content consistently reduced workability and compressive strength. At 7 days, compressive strength decreased from 5.40 MPa to 4.10 MPa and 2.15 MPa for 2% and 4% fiber additions, respectively. These findings confirm that untreated durian peel fiber is unsuitable for structural concrete but may be suitable for non-structural applications after material modification.